The Influence of Personal Branding and Adversity Quotient on Work Readiness of Final Year Students Through Mediation of Self-Efficacy - Siti Nurun Chumairoh; Choirul Anam; Fonny Dameaty Hutagalung; Andika Putranta Utama (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2026)
Objective: This study aims to examine the influence of personal branding and adversity quotient on the work readiness of final-year students, with self-efficacy acting as a mediating variable. The research emphasizes the urgency of preparing students for the competitive labor market amid Indonesia's rising unemployment rates among graduates. Method: Using a quantitative approach, data were collected from 287 senior students at the Faculty of Economics and Business, Malang State University, via structured questionnaires on a 5-point Likert scale. Structural Equation Modeling with SmartPLS 4.1.0 was employed to analyze the relationships between variables, including the assessment of validity, reliability, and hypothesis testing. Results: Findings indicate that personal branding significantly influences self-efficacy (β= 0.167, p < 0.001), which in turn significantly impacts work readiness (β= 0.430, p < 0.001). Personal branding does not have a direct significant effect on work readiness (p > 0.05). Conversely, adversity quotient directly affects both self-efficacy (β= 0.674, p < 0.001) and work readiness (β= 0.308, p < 0.001). The model explains 36.9% of the variance in work readiness. Novelty: This research is the first post-pandemic study in Indonesia to investigate these internal psychological factors among final-year students, highlighting the crucial role of resilience and self-confidence over external branding in fostering graduate preparedness. The study provides insights into internal resilience strategies as a means to improve employability, urging higher education institutions to prioritize psychological development in career readiness programs.